3-(2, 6-Dichloro-benzyloxy)-11-oxo-olean-12-ene-29-oic acid, a semisynthetic derivative of glycyrrhetic acid: synthesis, antiproliferative, apoptotic and anti-angiogenesis activity12. Issue 4 (11th December 2014) - Sharma, Rajni; Guru, Santosh K.; Jain, Shreyans K.; Pathania, Anup Singh; Vishwakarma, Ram A.; Bhushan, Shashi; Bharate, Sandip B.
Abstract : The synthesis and biological evaluation of the semisynthetic analogs of glycyrrhetic acid are described. Abstract : Glycyrrhetic acid (2, 3β-hydroxyl-11-oxo-olean-12-ene-29-oic acid), a pentacyclic triterpenoid isolated from Glycyrrhiza glabra, is known to possess a wide range of biological activities. Herein, we report the synthesis and antiproliferative activity of 3- O -ether derivatives of glycyrrhetic acid. The cytotoxicity of the prepared derivatives was investigated in three cancer cell lines, including human pancreatic (MIAPaCa-2), prostate (PC-3) and human hepatocellular liver carcinoma (HepG-2). Amongst the tested compounds, the 2, 6-dichlorobenzyl5b and 2, 4-dichlorobenzyl derivative5r displayed significant cytotoxicity in PC-3 cells with IC50 values of 6 and 18 μM, respectively. The dichlorobenzyl derivative5b also displayed cytotoxicity in MIAPaCa-2 (IC50 : 7 μM) and HepG-2 cells (IC50 : 19 μM). Further, compound5b was investigated for apoptosis-induction by cell cycle analysis, nuclear morphological changes and mitochondrial membrane potential loss in PC-3 cells. Compound5b led to an increase in the sub-G1 population in PC-3 cells, which is indicative of its apoptotic properties. Interestingly, compound5b also arrested the S-phase of the cell cycle. The nuclear morphology of PC-3 cells after treatment with compound5b was also investigated which confirmed the formation of apoptotic bodies. Compound5b induced apoptosis through both intrinsic and extrinsic apoptotic pathways in PC-3 cells, which was confirmed by mitochondrial membrane potential loss, inhibition of pro-caspase-3, 8 and 9 and cleavage of PARP-1. Furthermore, there was a significant decrease in the Bcl-2/Bax ratio induced by compound5b in PC-3 cells. Interestingly, compound5b also inhibited the VEGF-induced PC-3 cell migration and decreased the wound closure percentage from 100 to 12% at 30 μM. Similarly, compound5b inhibited the angiogenesis-dependent cell migration in HUVEC cells and decreased wound closure from 100 to 20% at 30 μM, indicating its anti-angiogenic activity.